AN ANALYSIS ON NOVEL “THE ZAHIR” BY PAULO COELHO - Firinta Togatorop; Asima Rohana Sinaga (English Department, University of Riau Kepulauan, Batam,Indonesia, 2021)
The objective of this research was to know an analysis on Novel “ The Zahir” By Paulo Coelho about plots, the main characters, the settings, the purpose, the style and tone, the symbols, the structural and sense devices, and the theme. This research was a descriptive qualitative design that would do library research because it attempted to find out and to explain the literary elements of novel “The Zahir” by Paulo Coelho (2005) based on theory of X.J. Kennedy (1991) and L.G. Alexander (1979). The method of collecting the data in qualitative research used Triangulation. All the data was analyzed based on the related theories. The novel was about a free man Paulo Coelho with full of obsession on looking his Zahir Esther because of his mistakes in past time. In the beginning, the story told about Esther struggled to change Paulo Coelho’s freedom by making him to be famous writer. The middle part told about Paulo was left by his wife. The ending part told about his efforts to look for her wife until he could find Esther in Kazakhstan. The purpose of the novel was to tell us that we had to appreciate our beloved person.